Les différentes relations entre le verbal et le visual sur l’exemple des journaux télévisés - Borowczyk, Paulina (Studia Romanica Posnaniensia, 2017)
The article presents that the sense of verbal-visual messages is a result of various relations between text and images (parallel, supplementing and interpretative meaning, equivalence and contradiction). The author tries to show what type of relations is present in the French-German news that has to be translated for foreign recipient and to observe how images can influence the decisions of a translator in this type of texts.